2000
DOI: 10.1063/1.480547
|View full text |Cite
|
Sign up to set email alerts
|

State-to-state rotational excitation of CO by H2 near 1000 cm−1 collision energy

Abstract: Relative state-to-state rotationally inelastic cross sections for excitation of carbon monoxide by hydrogen were measured in a crossed molecular beam experiment at collision energies 795, 860, and 991 cm Ϫ1 . The results are compared to predictions of a recent ab initio potential energy surface ͓J. Chem. Phys. 108, 3554 ͑1998͔͒. The agreement is very good. A comparison with older data on thermally averaged total depopulation cross sections ͓Chem. Phys. 53, 165 ͑1980͔͒ indicates that the absolute magnitudes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…already found that the two treatments lead to essentially the same agreement with the results for rotational excitations of CO measured in a crossed-beam experiment at collision energies near 1000 cm −1 in ref. 12, and our findings are the same. In the case of vibrational deexcitation, one has to use a surface with at least the C-O distance dependence, so only the effects of including or not the H-H separation can be investigated.…”
Section: Discussionsupporting
confidence: 86%
“…already found that the two treatments lead to essentially the same agreement with the results for rotational excitations of CO measured in a crossed-beam experiment at collision energies near 1000 cm −1 in ref. 12, and our findings are the same. In the case of vibrational deexcitation, one has to use a surface with at least the C-O distance dependence, so only the effects of including or not the H-H separation can be investigated.…”
Section: Discussionsupporting
confidence: 86%
“…The implementation of the modified JS-potential into the MOLSCAT code was done by McBane [10]. The quantum-scattering calculations were performed using the CC method and the hybrid modified logderivative Airy integrator [11] …”
Section: Quantum Scattering Calculationsmentioning
confidence: 99%
“…State-to-state cross sections for rotational excitation of CO(v 1 = 0, j 1 = 0, 1) by collisions with H 2 . Theoretical results of full-dimensional calculations on V6D and 4D rigidrotor calculations on V12 are compared with normalized experimental results[40] for collision energies of (a) 795 cm −1 , (b) 860 cm −1 , and (c) 991 cm −1 . The calculations were performed for H 2 (v 2 = 0, j 2 = 0), but the experimental H 2 rotational distribution was undetermined.…”
mentioning
confidence: 99%
“…The calculations were performed for H 2 (v 2 = 0, j 2 = 0), but the experimental H 2 rotational distribution was undetermined. The error bars correspond to twice the estimated standard deviation in the weighted means of the measurements[40].…”
mentioning
confidence: 99%